Corporate Crime in Smuggling Illegal Foreign Workers in Indonesia - Fitri Yanni; Zulyadi, Rizkan; Syaputra, M. Yusrizal Adi (Veteran Law Review, 2023)
The globalization era facilitates the mobilization of workers across borders, resulting in the influx of foreign workers (TKA) into Indonesia. The employment of TKA aligns with the nation's goals of enhancing investments, technology transfers, and expertise to Indonesian Citizen Workers (TKI) while broadening employment prospects. Per the Job Creation Law No.11 of 2020, Article 45 paragraph (1) stresses the necessity of assigning TKI as companions for foreign workers. This mandate emphasizes training to facilitate technology and skill transfer from foreign workers to TKI companions. Employing the standard legal approach, this study aims to evolve legal theories through a rigorous scientific process. It involves scrutinizing legal documents to explore the regulatory framework and theories relevant to contemporary issues. Utilizing a descriptive analytical method, this research interprets and correlates legal statutes and theories with present concerns. Findings, employing a deductive approach, point to the classification of illegal foreign workers and the necessary sanctions for companies involved in illegal labor trafficking. Illegal foreign workers breach migration regulations, while companies partaking in unlawful labor trafficking face stringent penalties like imprisonment, fines, and license revocation. This study underlines the imperative to enforce legal measures to curb illegal labor practices and protect the nation's labor integrity.